Título Padrão - Ferreira, Luciane Augusto de Azevedo (Arquivos de Ciências do Mar, 2019)
New records and extensions of the distribution range of seven species of porcellanid crabs, representing four genera, are reported in the West Indian Islands: Megalobrachium mortenseni, M. poeyi, M. roseum, Pachycheles ackleianus, P. riisei, Petrolisthes rosariensis and Porcellana sayana. The analyzed species are deposited in the National Museum of Natural History, Smithsonian Institution, and the American Museum of Natural History. It is provided new records from Bahamas, Jamaica, Haiti, Dominican Republic, Puerto Rico, Antigua and Barbuda, St. Vincent and The Grenadines and Trinidad and Tobago. Diagnostic characters and ecological notes are given for each species. Keywords: Biodiversity, Caribbean islands, range extension, porcelain crabs, west Indies.